Examining the Diversity of Corporate America and the Federal Government: A Comparison of Selected Sectors - Malone, Duvalier (Archives of Business Research, 2023)
Managing diversity has become a fundamental priority of leading U.S. firms. Management of modern businesses must address the issue of employee diversity. Concomitantly, managing rising diversity demands greater consideration in governmental, corporate, and nonprofit enterprises. The researchers explore the effects of diversity and diversity management on employee views of organizational performance in U.S. federal agencies by establishing measures of three variables: diversity, workplace diversity, and perceived performance of the organization. Despite the fact that the motivations and practices of diverse companies are similar to those described in the best-practices industry, following these guidelines may not guarantee that a company will reach a high degree of diversity. A firm's level of diversity may be influenced as much by contextual factors like its industry affiliation and company size as by strategic factors. However, racial diversity does correlate favorably with organizational performance when tempered by diversity practices and group performance. Diverse perspectives on gender and age and the connections between these factors and other environmental factors lead to inconsistencies.